UMP feted staff who completed their studies and the university’s retirees - UMP, PNC (2019)
Universiti Malaysia Pahang (UMP) feted 28 staff and fellows who had completed their PhD studies in 2018 as well as staff who had retired in an event held at Tun Abdul Razak Chancellery Banquet Hall in UMP Pekan Campus on December 19, 2018.